2021
DOI: 10.1007/s11858-021-01295-6
|View full text |Cite
|
Sign up to set email alerts
|

Elementary teachers’ reflections on their use of digital instructional resources in four educational contexts: Belgium, Finland, Sweden, and U.S.

Abstract: We examine teachers' reflections on incorporating digital instructional resources (DIRs) into their mathematics teaching. We analyze qualitative interviews with 39 elementary school teachers from four educational contexts: Belgium, Finland, Sweden, and the U.S., using a framework proposed by Pepin et al. (2017) to consider opportunities for DIRs to shift elements of teaching and learning in potentially transformative ways. Teachers described three major domains of teaching practice where they used DIRs: a) cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…The transformative potential of technology noted by Remillard et al (2021) was acknowledged across schools. For all teachers the minimum of internet connectivity with a basic device to access WhatsApp and other digital resources were noted as essential for enabling continued homebased learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transformative potential of technology noted by Remillard et al (2021) was acknowledged across schools. For all teachers the minimum of internet connectivity with a basic device to access WhatsApp and other digital resources were noted as essential for enabling continued homebased learning.…”
Section: Discussionmentioning
confidence: 99%
“…Remillard et al’s ( 2021 , p. 1331) study across four countries showed that “participation in social media and resource sharing altered the nature of and ways teachers participated in their own professional learning” and argued that digital resources have transformative potential in teaching and learning. They described three major domains of digital resource use, namely, class instruction, learner practice, and professional learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is mirrored in a growing attention to these socio-cultural practices in research on the implementation of reform through curriculum resources, which is also apparent in this special issue. First, Remillard et al, (2021, this special issue) examined teachers' reflections on incorporating digital instructional resources into their mathematics instruction. They were particularly interested in how digital instructional resources might shift elements of teaching and learning in potentially transformative ways.…”
Section: Types Of 'Use' By Teachersmentioning
confidence: 99%
“…Research related to the implementation of PHET media combined with PBL about improving the mathematical critical thinking and problem solving ability has been conducted by several researchers. For example, research conducted by , Remillard et al, (2021) and Rezat (2021). In general, the researchers concluded that PBL, which is collaborated with learning media that are presented visually and interactively to students, will be more easily accepted by students in digesting learning materials.…”
Section:  Introductionmentioning
confidence: 99%